ANALISIS FENOMENA ELECTROHYDRODYNAMIC PADA PERMUKAAN MINYAK SILIKON (CAIRAN DIELEKTRIK) MENGGUNAKAN SISTEM PEMBANGKIT PLASMA LUCUTAN PIJAR KORONA NEGATIF DENGAN ELEKTRODA BERKONFIGURASI TITIK BIDANG - Nur, Muhammad; Anam, Choirul; Arisa, Betri (BERKALA FISIKA, 2007)
An analysis of Electrohydrodynamic (EHD) phenomenon deformation of oil silicon surface has been done.The negative corona glow discharge plasma in this research is generated by plasma generator system in point to plane electrodes configuration. The first step of experiment is to determine correlation of voltage and electric current, and correlation of distance between electrode and electric current. Then, the second is to determine correlation of voltage and hole radius of oil silicon surface, and corelation of distance between electrode and hole radius of oil silicon surface. Finally, it is to determine  the velocity hole for back to initial position of oil silicon surface after turn off electric field. The EHD phenomenon of oil silicon can be generated by impose of non homogeneous high electrics field. The voltage of corona at distance between electrodes 1 cm, 1,5 cm and  2 cm are 2,6 kV-4 kV,  3,4 kV-5,2 kV, and  3,8 kV-6,0 kV respectively. The increase of electrics field intensity influence dipole moment strength, it increases the radius of the hole of oil silicon surface. The increase of distance between electrode influence parabolic angle of electrics line field then cause the increase of hole radius. After this, if the electric field is zero with  increasing voltage, velocity hole of  oil silicon for back to initial position  slower then if the increasing of h, that makes the velocity hole for back to initial position faster.   Key words: Electrohydrodynamic, Silicon Oil, Dielectric polarization, Positive corona glow discharge plasma, ionic wind.